Variação vertical diária de larvas de peixes na várzea Amazônica Central, Brasil - RAMOS, Arthur Souza (2019)
The daily vertical migration is a pattern of behavior widely studied in marine ecosystems. However, there are few studies few of freshwater fish, especially in the early stages of development. In this context, this study aims to investigate the vertical variation of the assemblies of fish larvae in ponds and floodplain environments channels on Sustainable Development Reserve Mamirauá (RDSM), in relation to different times of the hydrological cycle. Samples were collected during times of flood, wet, ebb and dry using a conical net (300), by means of horizontal drag on the water column surface and depth, during the daily cycle in 2011. Analysis the results indicate that the vertical migration occurred during all times of the hydrological cycle and study sites, with the highest densities ever occurring on the surface during the night. These results are of great importance to define seasonal strategies for the protection of floodplain environments, revealing that daytime sampling underestimate the ichthyoplankton parameters for several species, crucial to maintaining the ichthyic diversity of all the average Solimões region and the conservation of important fish stocks commercially exploited in this part of the Amazon.